PENINGKATAN EFISIENSI BIAYA PENGOLAHAN LIMBAH PERUSAHAAN MENGGUNAKAN TARGET COSTING DENGAN VALUE ENGINEERING - Istikhoroh, Siti; Ardhiani, Mutiara Rachma (Majalah Ekonomi, 2019)
Companies in the modern industry are fully aware that environmental and social issues are also an important part of the company. Waste treatment costs reflect the company's commitment to minimize negative impacts due to its operational activities. one way companies can do to save costs is cost reduction. Cost reduction is achieved not only through attractive product designs, but also through improvements in the efficiency of the production process. Costs that have no added value are expected to be reduced by carrying out value engineering. Value engineering is used to design products at lower costs by reviewing the functions desired by the customer. After carrying out value engineering, functions and performance are maintained in accordance with what has been set by the company.